Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Konsumen Olahan Susu Di Koperasi Susu SAE Pujon - Inda Nur Hikmah (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
SAE Pujon Milk Cooperative in one of the major dairy producers in Malang Regency. This study aims to determine the effect of product quality and brand image on consumer purchasing decisions of processed milk in the SAE Pujon Milk Cooperative. This type of research isverification or quantitative research. The population in this study are consumers who buy and consume dairy. The number ofsamples is 30 respondents using multiple linier regression. This research uses descriptive quantitative analysis and statistical analysis which is used to determine the direct relation between variable product quality, brand image, and purchase decision. Research results show that (1) product quality influence partially on purchasing decisions in dairy consumers in SAE Dairy Cooperative (2) brand image influence partially on purchasing decisions to consumers of processed milk in the SAE Pujon Coorperative (3) product quality and brand image jointly influence the purchasing decisions of consumers of processed milk in the SAE Pujon Milk Cooperative. Keywords: Product Quality; Brand Image; Purchase Decision